2023
DOI: 10.1097/wco.0000000000001135
|View full text |Cite
|
Sign up to set email alerts
|

Sudden unexpected death in epilepsy

Abstract: Purpose of reviewSudden unexpected death in epilepsy (SUDEP) is a leading cause of death in patients with epilepsy. This review highlights the recent literature regarding epidemiology on a global scale, putative mechanisms and thoughts towards intervention and prevention.Recent findingsRecently, numerous population-based studies have examined the incidence of SUDEP in many countries. Remarkably, incidence is quite consistent across these studies, and is commensurate with the recent estimates of about 1.2 per 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 151 publications
0
4
0
Order By: Relevance
“…While deaths generally occurred following seizures, it is not clear if these are seizure-related deaths consistent with sudden unexpected death in epilepsy (SUDEP). 8 As they demonstrated, there are many progressive neuroanatomical changes in these mice that could contribute to increased mortality. 4 More work to dissect factors associated with mortality in this model will be needed.…”
Section: Commentarymentioning
confidence: 97%
“…While deaths generally occurred following seizures, it is not clear if these are seizure-related deaths consistent with sudden unexpected death in epilepsy (SUDEP). 8 As they demonstrated, there are many progressive neuroanatomical changes in these mice that could contribute to increased mortality. 4 More work to dissect factors associated with mortality in this model will be needed.…”
Section: Commentarymentioning
confidence: 97%
“…Stimulation of the amygdala has been associated with the induction of apnea [15][16][17] and ictal apnoa occurring in the postictal period has been particularly linked with SUDEP. 8,79,80 Recently, in a study of 73 epilepsy patients with recorded focal to bilateral tonic-clonic seizures and postconvulsive central apnea, increased amygdala volume and reduced NDI were observed, linking functional changes with microstructural alterations. 7 In the current study, we identified a correlation between amygdala mTOR pathway activation and MAP2 neuronal labeling and PCCA and GS frequency.…”
Section: Glioneuronal Hamartomamentioning
confidence: 99%
“…4,7 There is evidence from neuropathology, in vivo imaging, and neurophysiology that amygdala dysfunction is associated with an increased risk of SUDEP. 8 Pathology studies of the amygdala in SUDEP report subtle alterations of neuronal, interneuronal, glial, and serotonergic networks. [9][10][11][12] Nonaggregated neuronal tau accumulation and phosphorylation have also been reported in TLE, 13 and although this has not been systematically investigated in the amygdala, studies of animal models of Dravet syndrome with a high risk of SUDEP have shown that tau reduction reduced both epilepsy and SUDEP incidence.…”
Section: Introductionmentioning
confidence: 99%
“… 1 While mechanisms for SUDEP are only beginning to be understood, there is evidence that, in many cases, seizures negatively influence neural circuits and networks to lead to death by dysregulating breathing, cardiac and autonomic function, or arousal mechanisms. 2 One way that seizures may impact these distant network nodes is via spreading depolarization (SD); a wave of cellular depolarization that moves outward from the injury or seizure focus. 3 Direct current (DC) recordings are required to detect SD.…”
Section: Commentarymentioning
confidence: 99%